Benchmarking and regulation of power distribution companies in Pakistan. (May 2016) - Zakaria, Muhammad; Noureen, Rabia
Abstract: Using stochastic frontier analysis the study examines the cost effectiveness of electricity distribution utilities in Pakistan. For this purpose cost (in)efficiency is calculated for 8 distribution utilities using data for the period 2003–2013. The findings reveal that on average there is 72.5% efficiency in the electricity distribution sector. It indicates that electricity distribution utilities in Pakistan are cost inefficient by 27.5%. It is also found that quality of service affects efficiency. The results imply that there is significant potential to improve efficiency of electricity distribution utilities and that quality of service should be incorporated as part of efficiency of the electricity distribution utilities in Pakistan.